Theory of femtosecond coherent anti-Stokes Raman backscattering enhanced by quantum coherence for standoff detection of bacterial spores - Ooi, Chong Heng Raymond; Scully, M.O.; Beadie, G.; Kattawar, G.W.; Reintjes, J.F.; Rostovtsev, Y.; Zubairy, M.S. (2005)
Backscattered signal of coherent anti-Stokes Raman spectroscopy can be an extremely useful tool for remote identification of airborne particles, provided the signal is sufficiently large. We formulate a semiclassical theory of nonlinear scattering to estimate the number of detectable photons from a bacterial spore at a distance. For the first time, the theory incorporates enhanced quantum coherence via femtosecond pulses and a nonlinear process into the classical scattering problem. Our result shows a large backscattered signal in the far field, using typical parameters of an anthrax spore with maximally prepared vibrational coherence. Using train pulses of 1 kHz of repetition rate each with energy of 10 mJ, we estimate that about 10(7) photons can be detected by a 1 m diameter detector placed 1 km away from the spore in the backward scattering direction. The result shows the feasibility of developing a real time remote detection of hazardous microparticles in the atmosphere, particularly biopathogenic spores.